Organizational Knowledge Development - Dinca, Mihaela (Journal of Knowledge Management Practice, 2011)
The article focuses on the ways of creating knowledge within economic organizations. It deals with research and development, revealing the positive impact of research cooperation and enhancing knowledge workers and it also presents the barriers that can burden the knowledge development process. The article emphasizes as well the modalities of knowledge emergence, such as knowledge sharing, creativity and problem solving.
Keywords: knowledge management; Knowledge creation context; Research and development; Knowledge worker; Creativity; Problem solving